Assessing genetic diversity in Ziziphus jujuba 'Jinsixiaozao' using morphological and microsatellite (SSR) markers. (August 2015) - Zhang, Zhendong; Gao, Jiao; Kong, Decang; Wang, Aihua; Tang, Shizhe; Li, Yingyue; Pang, Xiaoming
Abstract: Ziziphus jujuba 'Jinsixiaozao' is one of the most elite Chinese jujube variety with a long cultivation history. There are many different types and newly developed accessions of 'Jinsixiaozao' reported, however the names are in chaotic. For the accurate identification of the accessions and estimating the genetic diversity, the diversity and relationships of the 45 'Jinsixiaozao' accessions were evaluated by 49 morphological traits and 24 highly polymorphic genomic SSR primers. The UPGMA dendrogram based on morphological traits separated the accessions into four major groups with Euclidean distance ranging from 4.26 to 12.26. Six of 24 SSR primers produced polymorphic patterns with a total of 17 alleles. Cluster analysis using UPGMA and Jaccard's coefficient grouped the accessions into eight groups. The SSR markers failed to distinguish the majority of the analyzed accessions, and a negative percentage of variation was partitioned. These results indicated low genetic diversity among the collected accessions. The mantel test revealed a weak negative correlation (r = −0.051) between the morphological dissimilarity matrix and that based on SSR markers. Highlights: Ziziphus jujuba 'Jinsixiaozao' is one of the most elite Chinese jujube variety with a long cultivation history in China. Forty-nine morphological traits and 24 SSR primers were used to evaluate the diversity and relationships of the 45 'Jinsixiaozao' accessions. The results provided useful information for future germplasm collections, conservation and breeding studies for 'Jinsixiaozao'.